2014
DOI: 10.1371/journal.pone.0108940
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy or Targeted Therapy as Second-Line Treatment of Advanced Gastric Cancer. A Systematic Review and Meta-Analysis of Published Studies

Abstract: Chemotherapy is a cornerstone in treatments of gastric cancer, but despite its benefit, less than 60% of patients receive salvage therapy in clinical practice. We performed a systematic review and meta-analysis based on trial data on the role of second-line treatment of advanced gastric cancer. MEDLINE/PubMed and Cochrane Library were searched for randomized phase III trials that compared active therapy to best supportive care in advanced gastric cancer. Data extraction was conducted according to the PRISMA st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 24 publications
0
50
0
4
Order By: Relevance
“…Performance status was reported to be a predictor of response to chemotherapy [17]. A recent metaanalysis suggests that patients with PS 0 have better survival after chemotherapy than those with PS 1 [18]. Among patients who received second-line therapy in the present study, 61.6% discontinued treatment because of disease progression and 46 patients (23.2%) received third-line treatment, highlighting the need for more clinical trials in advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Performance status was reported to be a predictor of response to chemotherapy [17]. A recent metaanalysis suggests that patients with PS 0 have better survival after chemotherapy than those with PS 1 [18]. Among patients who received second-line therapy in the present study, 61.6% discontinued treatment because of disease progression and 46 patients (23.2%) received third-line treatment, highlighting the need for more clinical trials in advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 62%
“…Other recent studies have reported a survival advantage associated with treatment with a second-line taxane such as docetaxel, or with irinotecan for cancers refractory to fluoropyrimidine and platinum treatment when compared to BSC [13,14]. In addition, no single agent option has been shown to be better than another in the second-line setting [18,23]. In our data, there appeared to be a trend in the increased use of taxanes as second-line therapy in 2012 relative to earlier years of the study (2009-2011); however, taxanes were prescribed to less than 20% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…10,[16][17][18] Concerning the second-line treatment, available data on the safety and efficacy of therapy are limited. 19 In particular COUGAR-02, a phase III randomized clinical trial, reported a significant OS improvement for docetaxel versus best supportive care (BSC) with a median advantage of 1.5 months. 20 Regarding subsequent lines of treatment, BSC or recruitment in clinical trials (fit patients only) is considered as the best choice.…”
Section: Conventional Treatmentmentioning
confidence: 99%
“…27 At least one data-comparison in terms of survival, RR, or toxicity was reported in all selected RCTs, which were therefore deemed eligible for the end-point analysis. Summarizing the 22 trials included in final analyses: 19 were eligible for OS analysis (among them, we underlined, that: 9 were included in antiangiogenic analysis; 4 studies were included in anti-EGFR analysis; 3 studies were included in anti-HER2 analysis; single trials respectively investigating a MET inhibitor, mTOR inhibitor and a PARP inhibitor), 19 were eligible for PFS analysis (among them, we underlined, that: 10 were included in anti-angiogenic analysis; 4 studies were included in anti-EGFR analysis; 2 studies were included in anti-HER2 analysis; single trials respectively investigating a MET inhibitor, mTOR inhibitor and a PARP inhibitor), and 19 were evaluable for RR analysis (among them, we underlined, that: 9 were included in anti-angiogenic analysis; 4 studies were included in anti-EGFR analysis; 3 studies were included in anti-HER2 analysis; single trials respectively investigating a Hedgehog inhibitor, a mTOR inhibitor and a PARP inhibitor). Twenty studies were evaluable for toxicity.…”
Section: Studies Selectionmentioning
confidence: 99%
“…Число больных, которым назначают вторую линию лечения, варьирует в широком диапазоне. Если в исследовании REAL-2 доля пациентов, получивших вто-рую линию лечения, составила 14% [3], то в исследовании SPIRITS -75% [4], в повседневной практике эта цифра колеблется около 45% [5].…”
Section: Introductionunclassified